PENDIDIKAN ISLAM BAGI BURUH MIGRAN DALAM AMAL USAHA PIMPINAN CABANG ISTIMEWA MUHAMMADIYAH MALAYSIA - Amalia, Firda; Setiawan, Farid; Salsabila, Unik Hanifah; Falikah, Tri Yaumil (Muta'allim: Jurnal Pendidikan Agama Islam, 2022)
The work demans of migrant workers who are far from ktheir families often make them easily exposed to bad influences in their social environtment. Therefore, PCIM Malaysia provides islamic education to migrant workers so that they can fortify themselves from behavior that is far from Islamic religious values in carrying out its duties, PCIM Malaysia incountered a number of obstacles, but slowly these obstacles were overcome. The study aim to determine the efforts made by PCIM Malaysia in providing Islamic education for migrant workers through Muhammadiyah Charity Business, as well as obstacles and solutions. The research uses qualitative methods with primary data in the form of interviews and secondary data form literatur sources. The results and research are PCIM Malaysia assesing a number of efforts in providing Islamic education for migrant workers through several activities and charities. These efforts are to increase Islamic knowledge and avoid bad influences and promiscuity. As wellas the conclution that PCIM Malaysia has chosen several years in providing Islamic education for migrant workers, namely conducting training, building PAUD, TPA guidance studios, and contributing to the contruction of University of Muhammadiyah Malaysia (UMAM).